Microscopic polyangiitis: Modern concepts and treatment options - I. T. Murkamilov; K. A. Aitbaev; V. V. Fomin; I. O. Kudaibergenova; F. A. Yusupov; Zh. A. Murkamilova; T. V. Beketova (Научно-практическая ревматология)
The article summarizes the modern concepts of microscopic polyangiitis (MPA), a primary ANCA-associated systemic necrotizing vasculitis without immune globulin deposition (pauci-immune) that affects mainly small vessels, while granulomatous inflammation is absent. Necrotizing glomerulonephritis is very common and pulmonary capillaritis often occurs. MPA can cause rapidly progressive damage to organ systems. The modern possibilities of MPA treatment, primarily anti-B cell therapy with rituximab, are discussed.